Enabling LoRaWAN Resource Allocation - Moraes, Jean (2021)
LoRaWAN is a promising long-range wireless technology in the Internet of Things (IoT) applications. This technology works with high density being able to connect devices that have long-range communication, low cost, and lower energy consumption. However, the densification of the use of LoRaWAN in IoT services poses a series of challenges due to interference by simultaneous transmission on the same channel. In this context, this article presents a heuristic and an optimal model for allocating adaptive resources in LoRaWAN for IoT applications. The results obtained through simulations available that the heuristic CORRECT offers results to the optimum described by the model MARCO for use of the channel.